Sintomas somáticos da depressão: características sociodemográficas e clínicas em pacientes de Atenção Primária em Curitiba, Brasil - Zorzetto Filho, Dirceu [UNIFESP] (2009)
Purpose: Major depressive disorder (MDD) encompasses a variety of affective, cognitive, somatic and behavioural symptoms. Painful and somatic manifestations are quite common in depression and in some cases cognitive and affective symptoms might be concealed by several different physical complaints. Failure to recognize somatic symptoms as one of the components of depressive disorder results in an increase of the financial demands on the health system and can also lead to functional impairment. The aim of our study was to evaluate the occurrence and severity of somatic symptoms, which could not be explained on clinical grounds in a sample of patients suffering from major depressive disorder (single episode, recurrent or unspecified). Methods: Twohundred and one (201) patients who attended the out-patient clinic at the Primary Health Unit (PHU) of the Family Health Program in Curitiba, Paraná, Brazil, agreed to take part in the study and answered a questionnaire for screening of depressive symptoms (CES-D) and a scale for severity of somatic symptoms (PHQ-15). In the second phase of the study, 114 patients who scored Z 15 on CES-D and who were considered as possibly having MDD were interviewed, using the SCI-I/P for validation of the psychiatric diagnosis. The Electronic Medical File of the Municipal Department of Health of Curitiba was also reviewed in order to gather clinical data of the study subjects. Results: The results of our study disclosed a high prevalence of MDD (24.32%) in our Primary Health Unit. The main clinical presentation of depression was somatic complaints: in our sample, all the 69 patients diagnosed with major depressive disorder presented somatic symptoms. On average, each patient had eight somatic complaints which could either not be completely explained on clinical grounds or presented with weak evidence of clinical origin, which was six times higher than those subjects who were not depressed. Depressed patients complained that their symptoms significantly impacted their health and 82.6% considered those symptoms to be moderate or severe. Such somatic symptoms were also more frequent among women (ANOVA, p<0.0007). There was also an association between the subjective severity of symptoms and severity of the depressive disorder measured by SCID-I/P (chi-square = 6.9286; SD=2; p=0.031). In addition, the group of depressed patients presented a higher number of clinical evaluations than those in the control (not-depressed) group (Mann-Whitney; p<0.001). Conclusions: These results highlight the importance of screening for painful and somatic symptoms as an essential part of major depressive disorder, so that it should be correctly diagnosed in those patients attending a Primary Health Unit.